Study of Tra Ly river salt intrusion modeling for assessment of salt intrusion prediction - Hoang, Nguyen Van; Cong, Nguyen Thanh; Khang, Ung Quoc; Dao, Le Quang (Vietnam Journal of Earth Sciences, 2014)
Thai Binh province has the lowest ground surface among the Bac Bo plain provinces so sea water intrusion into itsrivers is strong, including Tra Ly river flowing through he province’s central region. The paper presents study of seawater intrusion into Tra Ly river by numerical modeling. The results have shown that sea waster intrusion into Tra Lyriver is specific and dependent upon the daily hydraulic conditions of the river along with tidal regime. For long periodaverage monthly hydraulic conditions of the river, the sea water intrusion scenario may be very much different from theactual specific daily hydraulic conditions. For 2012 year, sea water intrusion into Tra Ly river during January to April ismore severe than November and December. Although sea water intrusion strongly occurs during dry season, there aremany time intervals during January-April when the river water has salt concentration lower than 1ppt, which is well toserve domestic and agricultural water demand. The prediction model would have good role in construction of fresh waterpumping schedule from different locations of Tra Ly river in future. References Nguyễn Văn Hoàng, Lê Quang Đạo, Nguyễn Thị Thu Vân, Ứng Quốc Khang, 2011. Ảnh hưởng của nước biển dâng đến xâm nhập mặn nước sông Hồng. Tuyển tập báo cáo Hội nghị Khoa học và Công nghệ biển lần thứ V-20-22/10/2011. Quyển 5: Sinh thái, Môi trường và Quản lý biển, tr.465-474. Nguyễn Văn Hoàng, 2012. Báo cáo tổng kết Đề tài: Nghiên cứu, đánh giá tác động của biến đổi khí hậu tới tỉnh Thái Bình, đề xuất các giải pháp thích ứng, giảm thiểu thiệt hại. Viện Địa chất-Viện Hàn lâm Khoa học và Công nghệ Việt Nam. Các tài liệu khí tượng thủy văn lưu trữ tại Trung tâm Dự báo khí tượng thủy văn Trung ương năm 2013. Địa hình lòng sông Trà Lý, 2006. Tài liệu điều tra cơ bản Bộ Nông nghiệp và Phát triển Nông thôn. Hamrick, J. M., 1992. A three-dimensional environmental fluid dynamics computer code:Theoretical and computational aspects. The College of William and Mary, Virginia Institute of Marine Science, Special Report 317, 63 pp. Craig, Paul M., 2009. User’s Manual forEFDC_Explorer: A Pre/Post Processor for theEnvironmental Fluid Dynamics Code, DynamicSolutions-International, LLC, Knoxville, TN,November, 2009. EFDC-explorer web version.http://www.efdc-explorer.biz